Operation mode of integrated energy system considering behavior characteristics of multiple subsystems. Issue 4 (May 2021) - Gong, Chuanzheng; Lin, Linjia; Yan, Qibo; Tang, Chenghong; Ge, Yangyang; Luo, Gang; Zeng, Ming; Liu, Ximei
Abstract: With the deepening coupling of power, natural gas and thermal network, the operation mode of integrated energy system has gradually become a new research hotspot. In this paper, taking the park level electric-heat-gas integrated energy system as an example, based on the study of its main characteristics, a mathematical model for the optimal operation of the integrated energy system is constructed, which mainly considers the gas turbine, energy storage and other equipment, in order to realize the economic operation of the system.